Helicobacter pylori eradication treatment for gastric carcinoma prevention in asymptomatic or dyspeptic adults: systematic review and Bayesian meta-analysis of randomised controlled trials - Teruhiko Terasawa; Isao Miyashiro; Katsuaki Kato; Takaki Yoshikawa; Reo Takaku; Hiroshi Nishida (BMJ Open)
Objectives Recent meta-analyses of eradication therapy in Helicobacter pylori-infected adults reported significant reductions in gastric carcinoma risk. However, concerns about supporting unfocused screening and eradication programme in healthy, asymptomatic populations have arisen. We performed a systematic review and Bayesian meta-analysis to provide an accurate interpretation of randomised evidence on the preventive effectiveness of eradication therapy on gastric carcinoma risk.Methods We searched databases including PubMed, Cochrane Central and Embase for reference and citation tracking without language restrictions, from inception through 31 July 2018. Paired investigators independently selected randomised controlled trials (RCTs) comparing eradication therapy with placebo or no treatment for asymptomatic or dyspeptic H. pylori-infected adults with no previous gastric carcinoma. The main outcome was gastric carcinoma incidence; secondary outcomes included gastric carcinoma-specific, non-gastric carcinoma and all-cause mortality.Results A total of 5 population-based and 2 outpatient care-based RCTs involving 7303 adults were eligible. Eradication algorithms were heterogeneous, and unsuccessful eradication and reinfection were frequently observed. A Bayesian meta-analysis with competing risk outcomes found low-certainty evidence that eradication therapy might be more likely than control to reduce gastric carcinoma risk (HR=0.65; 95% credible interval (CrI) 0.41 to 1.0; I2=11%). The CrIs included the null effects across the subgroup and sensitivity analyses, apart from those based on particular models that excluded two RCTs that enrolled subjects with specific histological findings only (HR=0.55; CrI 0.30 to 0.89; I2=14%). The uncertainty of the average 41% risk reduction in gastric carcinoma-specific mortality included a clinically important mortality risk increase (HR=0.59 favouring eradication therapy; CrI 0.25 to 1.20; I2=13%; low certainty).Conclusions There is insufficient evidence to support or refute the effectiveness of eradication therapy in preventing gastric carcinoma in H. pylori-infected, high-risk populations. Rigorously conducted large RCTs of healthy infected adults only would provide evidence of the true efficacy of successful eradication.PROSPERO registration number: CRD42014009245.